Factors Associated with Psychological Distress among Women of African Descent at High Risk for BRCA Mutations. Issue 1 (27th June 2012) - Cukier, Yael R.; Thompson, Hayley S.; Sussner, Katarina; Forman, Andrea; Jandorf, Lina; Edwards, Tiffany; Bovbjerg, Dana H.; Schwartz, Marc D.; Valdimarsdottir, Heiddis B.
Abstract: Little is known about psychological distress among women of African descent who are at high risk for a BRCA mutation. This is a group for whom breast cancer risk reduction is critical due to the group's high rates of breast cancer mortality. Distress is important to consider as it may reduce the potential benefit of genetic counseling and negatively affect decision making related to risk reduction. The goals of the current study were to examine breast cancer‐specific distress and depressive symptoms in women of African descent at who are at high risk for a BRCA mutation and to identify background factors associated with these outcomes. Participants were 148 high‐risk African American and Caribbean women who were part of a larger study that offered participants BRCA counseling at no cost. Participants completed the Impact of Events Scale, which assessed breast cancer‐specific distress, and the Center of Epidemiological Studies‐Depression Scale, which assessed depressive symptoms. Results of analyses revealed that almost half of the sample achieved scores indicating high and clinically significant breast cancer‐specific distress, while almost one‐third had clinically significant depression scores. Results further showed that low income was significantly associated with cancer‐specific distress, while having a cancer diagnosis was significantly associated with depressive symptoms. These results underscore the need for targeted psychological support throughout the genetic risk assessment process for this particular high‐risk group.